Accurate chemical analysis of oxygenated graphene-based materials using X-ray photoelectron spectroscopy. (March 2019) - Kovtun, Alessandro; Jones, Derek; Dell'Elce, Simone; Treossi, Emanuele; Liscio, Andrea; Palermo, Vincenzo
Abstract: A simple, fast and general protocol for quantitative analysis of X-ray photoelectron spectroscopy (XPS) data provides accurate estimations of chemical species in graphene and related materials (GRMs). XPS data are commonly used to estimate the quality of and defects in graphene and graphene oxide (GO), by comparing carbon and oxygen 1s XPS peaks, obtaining an O/C ratio. This approach, however, cannot be used in the presence of extraneous oxygen contamination. The protocol, based on quantitative line-shape analysis of C 1s signals, uses asymmetric pseudo-Voigt line-shapes (APV), in contrast to Gaussian-based approaches conventionally used in fitting XPS spectra, thus allowing better accuracy in quantifying C 1s contributions from graphitic carbon (sp2), defects (sp3 carbon), carbons bonded to hydroxyl and epoxy groups, and from carbonyl and carboxyl groups. The APV protocol was evaluated on GRMs with O/C ratios ranging from 0.02 to 0.30 with film thicknesses from monolayers to bulk-like (>30 nm) layers and also applied to previously published data, showing better results compared to those from conventional XPS fitting protocols. Based uniquely on C 1s data, the APV protocol can quantify O/C ratio and the presence of specific functional groups in GRMs even on SiOx, substrates, or in samples containing water. Graphical abstract: Image 1